THU0162 Residual synovitis in ankles and feet detected by ultrasonography in patients with rheumatoid arthritis. (12th June 2018) - Inamo, J.; Kaneko, Y.; Sakata, K.; Takeuchi, T.
Abstract : Background: Twenty eight joints that are usually evaluated for disease activity score of rheumatoid arthritis (RA) do not include ankles and metatarsophalangeal joints. Although foot synovitis of patients in remission is clinically important in that it associates to relapse and worse physical function, 1 composite markers without an assessment of foot have demonstrated poor performance in detecting foot synovitis. 2 Objectives: The aim of this study was to investigate the frequency and impact of residual synovitis in ankles and feet in patients with RA. Methods: Patients with RA who underwent both physical examination and ultrasonography (US) on 44 joints including hands, fingers, ankles, and metatarsophalangeal joints between April 2016 and January 2018 in Keio University Hospital were enrolled. We compared patients with swollen joints of feet and ankles and those without, and then analysed those who did not have swollen joints by physical examination but were detected to have synovitis by US. Results: Sixty one patients were enrolled in the study. The mean age was 58.5 years old, the disease duration was 7.1 years, and 85% were female. Among them, 21 patients had joint swelling in feet and ankles and 40 patients did not by physical examination. The patients in the former group showed significantly higher disease activity (DAS28 4.0 vs 2.4, p<0.05), higher doctor visual analogue scale (VAS, 33 vs 8 mm, p<0.05) and higher serum matrix metalloproteinase (MMP)−3 (165 vs 51 mg/dL, p<0.05). In the 40 patients with no swollen joints in ankles and feet by physical examination, 24 (60%) had active synovitis detected by US in those joints (US positive group) and the other 16 patients showed no synovitis in ankles and feet by US (US negative group). Whereas age and disease duration were not different between two groups, body mass index tended to be higher in the US positive group than the US negative group. Although the majority of both groups were in remission according to DAS28, fewer patients in the US positive group achieved remission according to Boolean criteria (29% vs 63%, p<0.05). The residual disease activity in ankles and feet was reflected in pain visual analogue scale most sensitively (33 mm vs 9 mm, p<0.05). The discordance in global assessments between patient and estimator of more than 30 mm was significantly frequent in the US positive group than the US negative group (33% vs 6%, p<0.05). Conclusions: The residual synovitis in ankles and feet did not reflect in remission criteria by DAS28 but did by Boolean criteria. It caused a discordance in global assessments between patient and estimator. References: [1] Wechalekar MD, Lester S, Hill CL, Lee A, Rischmueller M, Smith MD, Walker JG, Proudman SM. Active Foot Synovitis in Patients With Rheumatoid Arthritis: Unstable Remission Status, Radiographic Progression, and Worse Functional Outcomes in Patients With Foot Synovitis in Apparent Remission. Arthritis Care Res (Hoboken)2016;68(11):1616–1623. [2] Wechalekar MD1, Lester S, Proudman SM, Cleland LG, Whittle SL, Rischmueller M, Hill CL. Active foot synovitis in patients with rheumatoid arthritis: applying clinical criteria for disease activity and remission may result in underestimation of foot joint involvement. Arthritis Rheum2012;64(5):1316–22. Disclosure of Interest: None declared